Nonalcoholic fatty liver disease and the gut microbiome: Are bacteria responsible for fatty liver?. Issue 6 (April 2019) - Dong, Tien S; Jacobs, Jonathan P
Over the last several years, a growing body of literature has linked the gut microbiome to human health and diseases such as obesity, metabolic syndrome, and nonalcoholic fatty liver disease (NAFLD). This paper will review the current literature investigating the influence of diets associated with metabolic disorders on the microbiome and how those changes promote susceptibility to metabolic disorders. It will then focus in-depth on the role of the gut microbiome in NAFLD. The review will highlight associations of microbial composition and function with progression of NAFLD in patients and discuss potential mechanisms that link the gut microbiome to NAFLD. Finally, it will address limitations of existing studies along with future directions for microbiome research in NAFLD, including potential microbe-related treatments. Impact statement: This invited minireview for the upcoming thematic issue on the microbiome addresses the role of the microbiome in nonalcoholic fatty liver disease (NAFLD). The incidence of NAFLD has increased greatly in recent years in parallel with the rise in obesity and is now believed to have a population prevalence of 20–40%. It is anticipated to soon become the primary cause of liver-related morbidity and mortality, and unfortunately, there are few treatment options. Therefore, there is a critical need for improved understanding of NAFLD pathophysiology to provide new avenues for therapeutic intervention. In this paper, we have reviewed evidence from human and animal model studies that have associated microbiome composition and microbial metabolites with development and progression of NAFLD. We have also discussed proposed mechanisms by which the microbiome could contribute to NAFLD pathogenesis and addressed future directions for this field.